Bimetal organic framework catalyst and preparation method thereof, modified diaphragm and lithium-sulfur battery
By using bimetallic organic frame catalyst In/Ga-MOF in lithium sulfur batteries, the problems of polysulfide shuttle effect, slow kinetics and low active sulfur utilization during the charging and discharging process are solved, and higher cycle stability and charge and discharge efficiency are achieved.
Patent Information
- Application Number
- CN202411780966.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-04-04
AI Technical Summary
During the charging and discharging process, lithium-sulfur batteries face problems such as polysulfide shuttle effect, slow sulfur redox reaction kinetics and low active sulfur utilization, resulting in rapid attenuation of battery capacity and poor circulation performance.
The bimetallic organic framework catalyst In/Ga-MOF is used to effectively capture and fix polysulfides through its highly adjustable porous structure and rich chemically active sites, inhibit their migration to the negative electrode, and accelerate the sulfur conversion process through electrocatalytic activity.
It improves the cycle stability and charge and discharge efficiency of lithium-sulfur batteries, extends the service life of the battery, and improves the rate performance and long-term stability of the battery.
Smart Images

Figure CN119751900A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium-sulfur batteries, and in particular to a bimetallic organic framework catalyst and a preparation method thereof, a modified diaphragm and a lithium-sulfur battery. Background Art
[0002] Lithium-sulfur (Li-S) batteries have a high theoretical energy density (≈2600Wh kg -1 ) and relatively low cost of sulfur cathode materials, it is considered a strong candidate for the next generation of energy storage devices. However, the practical application of Li-S batteries still faces many challenges, including: 1. Polysulfide shuttle effect: The intermediate products (Li2S n , 4≤n≤8) are easily dissolved and diffused into the electrolyte, resulting in the loss of positive electrode active materials and the occurrence of negative electrode side reactions; 2. The kinetics of sulfur redox reaction are slow: the electrochemical reaction process of sulfur involves complex multi-electron transfer, and the kinetics are slow, which limits the charge and discharge efficiency of the battery; 3. The utilization rate of active sulfur is low: sulfur-based materials are prone to form "dead sulfur" during the charge and discharge process, which further reduces the capacity and cycle performance.
[0003] The porous structure, functionalization potential and excellent performance of MOFs in electrochemical systems make them an important material choice for solving these problems. In the field of lithium-sulfur batteries, the application of MOFs is mainly concentrated in the following aspects:
[0004] 1. Adsorption of polysulfides and inhibition of the shuttle effect: Polysulfides (Li2S6, Li2S4, etc.) in lithium-sulfur batteries are easily soluble in the electrolyte and undergo a shuttle effect during the charge and discharge process. This phenomenon not only leads to the loss of active substances, but also deposits on the negative electrode to trigger side reactions, ultimately leading to rapid decay of the battery capacity. MOFs, with their adjustable pore structure and surface chemical properties, can effectively capture polysulfide molecules through physical adsorption or chemical bonding, reduce their diffusion in the battery, and inhibit the shuttle effect. For example, MOFs materials with strong Lewis acidity or rich in functional groups such as hydroxyl groups can form stable coordination bonds or hydrogen bonds with polysulfides, thereby playing a restraining role and avoiding excessive migration of polysulfides.
[0005] 2. Catalyze the conversion of polysulfides: The metal nodes in MOFs have high chemical activity and can be used as electrocatalysts to accelerate the conversion reaction process of sulfur and polysulfides. In lithium-sulfur batteries, sulfur is gradually converted into polysulfides until the final Li2S through a series of redox reactions, and these intermediate steps usually become bottlenecks in electrochemical performance due to their slow reaction kinetics. The metal active sites in MOFs can reduce the conversion energy barrier of polysulfides and accelerate the electrochemical reaction, thereby improving the charge and discharge efficiency and rate performance of the battery. In particular, multi-metal MOFs can further optimize the reaction path and improve the catalytic activity through the synergistic effect of different metals.
[0006] 3. Improve the structural stability of the sulfur positive electrode: Sulfur will undergo volume expansion during the charge and discharge process, resulting in instability in the electrode structure, which further affects the cycle life of the battery. The framework structure of MOFs can regulate the expansion behavior of sulfur to a certain extent, preventing the sulfur positive electrode material from cracking or falling off during the charge and discharge cycle. By introducing MOFs as the skeleton material of the sulfur positive electrode, the volume change of sulfur can be effectively alleviated, thereby maintaining the structural integrity of the electrode and extending the service life of the battery.
[0007] 4. Optimizing the interfacial reaction in the electrolyte system: MOFs can also optimize the interfacial reaction inside the battery by modifying the separator or electrolyte system in lithium-sulfur batteries. For example, the MOF-modified separator can be used as a functional layer, which can effectively block the migration of polysulfides to the negative electrode and accelerate the conversion of sulfur through electrocatalytic activity, thereby improving the overall performance of the battery.
[0008] The metal centers (such as Fe, Co, Ni, etc.) in existing MOFs, such as transition metal MOFs, have relatively weak interactions with sulfur, which leads to their polysulfide adsorption and inhibition performance in lithium-sulfur batteries; the ion mobility of transition metals is relatively poor, which makes their electronic conductivity and ionic conductivity in lithium-sulfur batteries relatively low. Although MOFs have a highly porous structure, the conductivity of transition metal MOFs is still a bottleneck that limits their application. Transition metal MOFs may experience structural collapse or failure in batteries at high voltages or charge and discharge cycles. Especially after long-term use, the redox stability of the metal center may be reduced, resulting in a decrease in the mechanical and chemical stability of the MOF. Summary of the invention
[0009] In order to solve at least one of the above technical problems and develop a catalyst material with better performance for use in lithium-sulfur batteries, the present application provides a bimetallic organic framework catalyst and a preparation method, a modified diaphragm and a lithium-sulfur battery.
[0010] On the one hand, the present application provides a bimetallic organic framework catalyst, which is an In / Ga bimetallic MOFs, having In and Ga bimetallic catalytic centers; and the structure is a four-pointed star.
[0011] Optionally, in the catalyst, the molar ratio of In to Ga is 1:5.8 to 11.6.
[0012] In the catalyst of the technical solution of the present application, indium usually presents a +3 valence, has a larger ionic radius and lower electronegativity, while gallium also exists in a +3 valence, but has a smaller ionic radius and a stronger electronegativity. As the ratio of indium to gallium changes, the electronic structure and coordination environment of the metal ions in MOFs will also change, thereby affecting their catalytic performance and stability. When the ratio of indium to gallium is close to 1:5, MOFs maintain a relatively regular crystal structure, but as the ratio increases, it causes lattice distortion or the formation of irregular crystals; in In / Ga bimetallic MOFs, when the molar ratio of In to Ga is 1:5.8 to 11.6, the overall performance of the catalyst is better.
[0013] In a second aspect, the present application provides a method for preparing the above catalyst.
[0014] S1, mixing trimesic acid and DMF, and stirring evenly for 10 minutes to obtain solution A;
[0015] S2, mixing indium nitrate hydrate, gallium nitrate hydrate and DMF, and stirring evenly for 10 minutes to obtain solution B;
[0016] S3. Rapidly add solution B to solution A, stir vigorously for 10 minutes to obtain a transparent solution, and pour it into a reactor; place the reactor in an oven at 80-100°C for 8-12 hours, then heat to 100-120°C and then heat for another 24 hours, wash, and vacuum dry in a 60°C oven for 12 hours to obtain a catalyst.
[0017] Optionally, the washing treatment is: centrifugal washing with DMF and anhydrous ethanol for 3 times respectively.
[0018] In a third aspect, the present application provides a lithium-sulfur battery modified diaphragm coating, comprising a binder, a conductive agent and the above-mentioned catalyst.
[0019] Optionally, the weight ratio of the binder, the conductive agent and the catalyst is 1:2:7.
[0020] Optionally, the binder is polyvinylidene fluoride, and / or the conductive agent is conductive carbon black.
[0021] In a fourth aspect, the present application provides a modified diaphragm for a lithium-sulfur battery, comprising a diaphragm and the above-mentioned coating, wherein the coating is coated on one side of the diaphragm.
[0022] Optionally, the diaphragm is a PP diaphragm.
[0023] In a fifth aspect, the present application provides a lithium-sulfur battery, comprising a positive electrode, a negative electrode and the modified diaphragm described above; the modified diaphragm is arranged between the positive electrode and the negative electrode, and the side coated with the coating faces the positive electrode.
[0024] In summary, the present invention includes at least one of the following beneficial technical effects:
[0025] 1. The catalyst In / Ga-MOF has a highly adjustable porous structure and abundant chemically active sites, which can effectively capture and fix polysulfides; In and Ga ions have good adsorption properties and can form strong chemical bonds with polysulfides, thereby inhibiting their migration to the negative electrode, reducing the shuttle effect, and thus improving the cycle stability of the battery;
[0026] 2. The In and Ga bimetallic catalytic centers in the catalyst In / Ga-MOF have excellent electrocatalytic performance and can catalyze liquid-liquid and liquid-solid conversions; this catalytic activity can effectively reduce the energy barrier in the sulfur conversion process, accelerate the conversion rate of polysulfides, and thus improve the rate performance and charge and discharge efficiency of the battery;
[0027] 3. The In and Ga central metals in the catalyst In / Ga-MOF have strong corrosion resistance and can maintain good chemical stability in the complex working environment of lithium-sulfur batteries. Compared with other materials, In / Ga-MOF is more capable of maintaining its structural integrity and functionality in multiple cycles, is less prone to degradation or dissolution, and can improve the long-term stability of Li-S battery operation. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is the XRD pattern of In / Ga-MOF prepared in Preparation Example 2;
[0029] Figure 2 XRD pattern of Ga-MOF prepared in Comparative Example 1;
[0030] Figure 3 This is the SEM image of In / Ga-MOF prepared in Preparation Example 2;
[0031] Figure 4 is a SEM image of the In / Ga-MOF material in Preparation Example 4;
[0032] Figure 5 This is a data diagram of the charge and discharge performance effect of the lithium-sulfur battery prepared in Application Example 1;
[0033] Figure 6 The data diagram of the charge and discharge performance effect of the lithium-sulfur battery prepared in Application Example 3;
[0034] Figure 7 This is a data diagram of the charge and discharge performance effect of the lithium-sulfur battery (In-MOF) prepared in comparative application example 2;
[0035] Figure 8 This is a data diagram of the charge and discharge performance effect of the lithium-sulfur battery (Ga-MOF) prepared in comparative application example 1;
[0036] Fig. 9 This is a data chart comparing the charge and discharge performance of the lithium-sulfur battery (NiFe-MOF) prepared in Application Example 3. DETAILED DESCRIPTION
[0037] In the technical solution of the present application, the applicant provides a bimetallic organic framework catalyst, which is In / Ga bimetallic MOFs, having In and Ga bimetallic catalytic centers; the structure is a four-pointed star.
[0038] The applicant also provides a method for preparing the above catalyst, comprising the following steps:
[0039] S1, mixing trimesic acid and DMF, and stirring evenly for 10 minutes to obtain solution A;
[0040] S2, mixing indium nitrate hydrate, gallium nitrate hydrate and DMF, and stirring evenly for 10 minutes to obtain solution B;
[0041] S3. Rapidly add solution B to solution A, stir vigorously for 10 minutes to obtain a transparent solution, and pour it into a reactor; place the reactor in an oven at 80-100°C for 8-12 hours, then heat to 100-120°C and then heat for another 24 hours, wash, and vacuum dry in a 60°C oven for 12 hours to obtain a catalyst.
[0042] The applicant also provides a lithium-sulfur battery modified diaphragm coating, which includes a binder, a conductive agent and the above catalyst.
[0043] The applicant also provides a modified diaphragm for a lithium-sulfur battery, comprising a diaphragm and the modified diaphragm coating, wherein the coating is coated on one side of the diaphragm.
[0044] The applicant also provides a lithium-sulfur battery, comprising a positive electrode, a negative electrode and the modified diaphragm described above; the modified diaphragm is arranged between the positive electrode and the negative electrode, and the side coated with the coating faces the positive electrode.
[0045] In view of the shortcomings of the existing transition metal MOF in lithium-sulfur batteries, the inventors believe that compared with transition metals, the application of p-block metal MOF in lithium-sulfur batteries shows some unique advantages:
[0046] 1. Stronger sulfur affinity: p-block metals such as indium and gallium have strong Lewis acidity and can more effectively form stable complexes with sulfur and its polysulfides, thereby inhibiting the dissolution and shuttle effect of LiPSs; this enhanced sulfur affinity helps to improve the cycle stability and energy efficiency of lithium-sulfur batteries.
[0047] 2. P-block metals such as indium and gallium have lower chemical reactivity and stronger oxidation resistance, which makes MOFs based on these metals more stable under the high voltage conditions of lithium-sulfur batteries and can withstand longer charge and discharge cycles without structural collapse;
[0048] 3. Metals such as indium and gallium have good electrical conductivity. After combining with organic ligands, they can form a relatively stable three-dimensional network structure, thereby providing good electronic and ion conduction paths and enhancing the electrical conductivity of MOF;
[0049] 4. P-block metal MOFs can provide more lithium ion storage sites through their unique pore structure and the properties of the metal center. Especially when used as sulfur carriers or conductive additives, they can effectively alleviate the volume expansion problem of sulfur.
[0050] The highly adjustable porous structure and abundant chemically active sites in the catalyst In / Ga-MOF of the present application can effectively capture and fix polysulfides. In and Ga ions have good adsorption properties and can form strong chemical bonds with polysulfides, thereby inhibiting their migration to the negative electrode, reducing the shuttle effect, and thus improving the cycle stability of the battery.
[0051] In / Ga-MOF, the In and Ga bimetallic catalytic centers have excellent electrocatalytic performance and can catalyze liquid-liquid and liquid-solid conversions. This catalytic activity can effectively reduce the energy barrier in the sulfur conversion process, accelerate the conversion rate of polysulfides, and thus improve the rate performance and charge-discharge efficiency of the battery. Most importantly, the metal center can be regulated from a single metal to a bimetallic, which is conducive to studying the catalytic activity between different metal centers in the same structure.
[0052] In / Ga-MOF, the In and Ga central metals have strong corrosion resistance and can maintain good chemical stability in the complex working environment of lithium-sulfur batteries. Compared with other materials, In-Ga-MOF is more able to maintain its structural integrity and functionality in multiple cycles and is not prone to degradation or dissolution, which is crucial for the long-term stable operation of Li-S batteries.
[0053] This application loads a composite of In / Ga-MOF, conductive agent and binder on the positive electrode side of the polypropylene diaphragm, physically restricts PSs by improving the pore size of the diaphragm itself, and synergistically suppresses the "shuttle effect" of PSs with the chemical adsorption and electrocatalytic performance of In / Ga-MOF loaded on the diaphragm to LiPSs, thereby improving the cycle stability of lithium-sulfur batteries. The technical principles are as follows:
[0054] 1. The prepared In / Ga-MOF has a corresponding three-dimensional hierarchical porous framework structure that provides the adsorption capacity and physical confinement of PSs. At the same time, it realizes the high-throughput transmission of lithium ions and the uniform deposition and protection of the lithium negative electrode;
[0055] 2. In / Ga-MOF with different metal centers has two catalytic centers, In and Ga, which can catalyze liquid-liquid and liquid-solid conversions respectively; based on these advantages, it exhibits outstanding electrochemical performance when applied to Li-S batteries.
[0056] The present application is further described in detail below with reference to the accompanying drawings and embodiments.
[0057] In the following examples of the present application, the main components involved, unless otherwise specified, were purchased from commercially available products.
[0058] Preparation Example 1
[0059] This preparation example is used to prepare a sulfur positive electrode, and the details are as follows.
[0060] 160 mg of S (sulfur) and 20 mg of CB (carbon black) were weighed in a weight ratio of 8:1, respectively, mixed and ground thoroughly, and then kept warm in a tubular furnace at 155° C. in a nitrogen atmosphere for 12 h to obtain a sulfur positive electrode material.
[0061] The prepared sulfur cathode material, polyvinylidene fluoride (PVDF) and carbon black (CB) were fully mixed and ground in a weight ratio of 8:1:1, transferred to a weighing bottle, added with an appropriate amount of NMP organic solvent, and stirred continuously for 12 h to form a uniform slurry.
[0062] The film was evenly coated on aluminum foil using a 200 μm scraper and then placed in a vacuum drying oven at 60° C. for 12 h to obtain a sulfur positive electrode.
[0063] Preparation Examples 2 to 4 are used to prepare In / Ga bimetallic organic framework catalysts, and the details are as follows.
[0064] Preparation Example 2
[0065] Trimellitic acid (H3BTC, 3.5 mmol) was added into a beaker containing DMF (48 mL) and stirred evenly for 10 minutes. This solution was recorded as solution A.
[0066] Add 0.1 mmol of indium nitrate hydrate (In(NO3)3·xH2O) and 0.58 mmol of gallium nitrate hydrate (Ga(NO3)3·xH2O) into a beaker containing DMF (12 mL), and stir evenly for 10 minutes. This is recorded as solution B.
[0067] Then, solution B was quickly poured into solution A and stirred vigorously for 10 minutes. The resulting transparent mixed solution was transferred to a 100 mL polytetrafluoroethylene reactor. Subsequently, the polytetrafluoroethylene reactor was placed in an oven at 80°C for 12 hours, then heated to 100°C and heated for another 24 hours. The final product was centrifugally washed three times with DMF and anhydrous ethanol (first washed three times with DMF, then washed three times with anhydrous ethanol), and vacuum dried in a 60°C oven for 12 hours to obtain In / Ga-MOF.
[0068] Figure 1 From the XRD diagram of In / Ga-MOF in Preparation Example 2, it can be observed that In / Ga-MOF exhibits obvious characteristic peaks of In-MOF and Ga-MOF, which fully demonstrates the successful preparation of the In / Ga-MOF structure.
[0069] Figure 2 is the SEM image of Ga-MOF material; Figure 3 is a SEM image of the In / Ga-MOF material in Preparation Example 2; Figure 2 and Figure 3 It can be seen that the morphology of Ga-MOF is a three-dimensional tetrahedral structure, while the SEM image of In / Ga-MOF shows a special four-pointed star morphology.
[0070] Preparation Example 3
[0071] Trimellitic acid (H3BTC, 3.5 mmol) was added into a beaker containing DMF (48 mL) and stirred evenly for 10 minutes. This solution was recorded as solution A.
[0072] Add 0.1 mmol of indium nitrate hydrate (In(NO3)3·xH2O) and 1.16 mmol of gallium nitrate hydrate (Ga(NO3)3·xH2O) into a beaker containing DMF (12 mL), stir evenly for 10 minutes, and record it as solution B.
[0073] Then, solution B was quickly poured into solution A and stirred vigorously for 10 minutes. The resulting transparent mixed solution was transferred to a 100 mL polytetrafluoroethylene reactor. Subsequently, the polytetrafluoroethylene reactor was placed in an oven at 80°C for 12 hours, then heated to 100°C and heated for another 24 hours. The final product was centrifugally washed 3 times with DMF and anhydrous ethanol, respectively, and vacuum dried in an oven at 60°C for 12 hours to obtain In / Ga-MOF.
[0074] Preparation Example 4
[0075] Trimellitic acid (H3BTC, 3.5 mmol) was added into a beaker containing DMF (48 mL) and stirred evenly for 10 minutes. This solution was recorded as solution A.
[0076] Add 0.1 mmol of indium nitrate hydrate (In(NO3)3·xH2O) and 0.1 mmol of gallium nitrate hydrate (Ga(NO3)3·xH2O) into a beaker containing DMF (12 mL), and stir evenly for 10 minutes. This is recorded as solution B.
[0077] Then, solution B was quickly poured into solution A and stirred vigorously for 10 minutes. The resulting transparent mixed solution was transferred to a 100 mL polytetrafluoroethylene reactor. Subsequently, the polytetrafluoroethylene reactor was placed in an oven at 80°C for 12 hours, then heated to 100°C and heated for another 24 hours. The final product was centrifugally washed 3 times with DMF and anhydrous ethanol, respectively, and vacuum dried in an oven at 60°C for 12 hours to obtain In / Ga-MOF.
[0078] Figure 4 This is the SEM image of the In / Ga-MOF material in Preparation Example 4.
[0079] Comparative Preparation Example 1
[0080] This comparative preparation example uses Ga-MOF.
[0081] Comparative Preparation Example 2
[0082] This comparative preparation example uses In-MOF.
[0083] Comparative Preparation Example 3
[0084] This comparative preparation example uses NiFe-MOF.
[0085] Examples 1 to 2 and Comparative Examples 1 to 3 are used to prepare modified separators for lithium-sulfur batteries, as follows.
[0086] Example 1
[0087] 70 mg of In / Ga-MOF prepared in Preparation Example 2, 20 mg of CB, and 10 mg of PVDF were weighed separately, mixed and ground thoroughly in a mortar, then transferred to a weighing bottle, an appropriate amount of NMP organic solvent was added, and stirred continuously for 12 hours, then evenly coated on the Celgard-2500 diaphragm with a 200 μm spatula, and transferred to an oven at 60°C for vacuum drying overnight to obtain a modified diaphragm.
[0088] Example 2
[0089] 70 mg of In / Ga-MOF prepared in Preparation Example 3, 20 mg of CB, and 10 mg of PVDF were weighed separately, mixed and ground thoroughly in a mortar, then transferred to a weighing bottle, an appropriate amount of NMP organic solvent was added, and stirred continuously for 12 hours, then evenly coated on the Celgard-2500 diaphragm with a 200 μm spatula, and transferred to an oven at 60°C for vacuum drying overnight to obtain a modified diaphragm.
[0090] Example 3
[0091] 70 mg of In / Ga-MOF prepared in Preparation Example 4, 20 mg of CB, and 10 mg of PVDF were weighed separately, mixed and ground thoroughly in a mortar, then transferred to a weighing bottle, an appropriate amount of NMP organic solvent was added, and the mixture was stirred continuously for 12 h. Then, the mixture was evenly coated on a Celgard-2500 diaphragm with a 200 μm spatula, and then transferred to an oven at 60° C. and vacuum dried overnight to obtain a modified diaphragm.
[0092] Comparative Example 1
[0093] 70 mg of Ga-MOF prepared in Comparative Preparation Example 1, 20 mg of CB, and 10 mg of PVDF were weighed separately, mixed and ground thoroughly in a mortar, then transferred to a weighing bottle, an appropriate amount of NMP organic solvent was added, and stirred continuously for 12 hours, then evenly coated on the Celgard-2500 diaphragm with a 200 μm spatula, and transferred to an oven at 60° C. and vacuum dried overnight to obtain a modified diaphragm.
[0094] Comparative Example 2
[0095] 70 mg of In-MOF prepared in Comparative Preparation Example 2, 20 mg of CB, and 10 mg of PVDF were weighed separately, mixed and ground thoroughly in a mortar, then transferred to a weighing bottle, an appropriate amount of NMP organic solvent was added, and stirred continuously for 12 hours, and then evenly coated on the Celgard-2500 diaphragm with a 200 μm spatula, and transferred to an oven at 60°C for vacuum drying overnight to obtain a modified diaphragm.
[0096] Comparative Example 3
[0097] 70 mg of NiFe-MOF prepared in Comparative Preparation Example 3, 20 mg of CB, and 10 mg of PVDF were weighed separately, mixed and ground thoroughly in a mortar, then transferred to a weighing bottle, an appropriate amount of NMP organic solvent was added, and stirred continuously for 12 hours, then evenly coated on the Celgard-2500 diaphragm with a 200 μm spatula, and transferred to an oven at 60° C. and vacuum dried overnight to obtain a modified diaphragm.
[0098] Application Examples 1 to 3 are used to apply the modified diaphragms prepared in the above Examples 1 to 3 to lithium-sulfur batteries; Comparative Application Examples 1 to 3 are used to apply the modified diaphragms prepared in the above Comparative Examples 1 to 3 to lithium-sulfur batteries;
[0099] The lithium-sulfur battery preparation process is as follows.
[0100] The cut sulfur cathode prepared in Preparation Example 1 and the modified separator prepared in Examples 1 to 3 / Comparative Examples 1 to 3 were placed in a glove box, and then a CR2032 button cell was assembled in the order of cathode shell, cathode, electrolyte, separator, electrolyte, anode, gasket, shrapnel and anode shell. The electrolyte used was 1M LiTFSI, DME:DOL=1:1V%, 2% LiNO3.
[0101] The charge and discharge performance of the button cell assembled above was tested at room temperature using the LandCT2001A battery test system and the CHI760E electrochemical workstation. The specific test results are shown in Table 1; the specific capacity / coulomb efficiency is the specific capacity / coulomb efficiency of the lithium-sulfur battery when the number of cycles is 50. The charge and discharge performance effect data of the lithium-sulfur battery prepared in Application Example 1 are shown in Table 1. Figure 5 As shown; the charge and discharge performance data of the lithium-sulfur battery prepared in Application Example 3 is as follows Figure 6 As shown;
[0102] Comparative Application Example 2 The charge and discharge performance data of the lithium-sulfur battery (In-MOF) prepared are as follows: Figure 7 As shown; Comparative application example 1 prepared lithium sulfur battery (Ga-MOF) charge and discharge performance effect data as shown Figure 8 As shown; Comparative Application Example 3 prepared lithium sulfur battery (NiFe-MOF) charge and discharge performance data as shown Fig. 9 As shown;
[0103] Table 1
[0104] Lithium-sulfur battery catalyst In / Ga molar ratio <![CDATA[Specific capacity / mAh·g -1 > Coulomb efficiency / % Application Example 1 In / Ga-MOF 1:5.8 805.0 99.89 Application Example 2 In / Ga-MOF 1:11.6 759.6 99.65 Application Example 3 In / Ga-MOF 1:1 662.7 98.82 Comparative application example 1 Ga-MOF / 614.8 99.53 Comparative Application Example 2 In-MOF / 592.4 99.63 Comparative Application Example 3 NiFe-MOF / 405.9 99.43
[0105] As can be seen from Table 1, the specific capacity of lithium-sulfur battery application examples 1 to 3 corresponding to the In / Ga-MOFs catalyst prepared in this application is significantly improved compared to the lithium-sulfur battery comparative application examples 1 to 3 corresponding to the Ga-MOF, In-MOF and NiFe-MOF catalysts. And the specific capacity of application example 1 is increased by nearly 100% compared to comparative application example 3.
[0106] The coulombic efficiency of lithium-sulfur battery application examples 1 to 2 is improved compared with comparative application examples 1 to 3, and the specific capacity is significantly improved. Therefore, in the technical solution of the present application, when the In / Ga molar ratio is 1:5.8 to 11.6, the prepared In / Ga-MOFs catalyst has better performance, and the corresponding lithium-sulfur battery has better performance.
[0107] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. A bimetallic organic framework catalyst, characterized in that: It is an In / Ga bimetallic MOFs with In and Ga bimetallic catalytic centers; the structure is a four-pointed star.
2. The catalyst according to claim 1, characterized in that The molar ratio of In to Ga is 1:5.8-11.
6.
3. A method for preparing the catalyst according to claim 1, characterized in that: S1, mixing trimesic acid and DMF, and stirring evenly for 10 minutes to obtain solution A; S2, mixing indium nitrate hydrate, gallium nitrate hydrate and DMF, and stirring evenly for 10 minutes to obtain solution B; S3. Rapidly add solution B to solution A, stir vigorously for 10 minutes to obtain a transparent solution, and pour it into a reactor; place the reactor in an oven at 80-100°C for 8-12 hours, then heat to 100-120°C and then heat for another 24 hours, wash, and vacuum dry in a 60°C oven for 12 hours to obtain a catalyst.
4. The preparation method according to claim 1, characterized in that: The washing treatment was as follows: DMF and anhydrous ethanol were centrifuged and washed three times respectively.
5. A lithium-sulfur battery modified diaphragm coating, characterized in that: The invention comprises a binder, a conductive agent and the catalyst as claimed in claim 1.
6. The coating according to claim 5, characterized in that The weight ratio of the binder, the conductive agent and the catalyst is 1:2:
7.
7. The coating according to claim 5, characterized in that The binder is polyvinylidene fluoride, and / or the conductive agent is conductive carbon black.
8. A modified separator for a lithium-sulfur battery, characterized in that: The invention comprises a diaphragm and the coating as claimed in claim 5, wherein the coating is coated on one side of the diaphragm.
9. The coating according to claim 8, characterized in that The diaphragm is a PP diaphragm.
10. A lithium-sulfur battery, characterized in that: The invention comprises a positive electrode, a negative electrode and the modified separator as claimed in claim 9; the modified separator is arranged between the positive electrode and the negative electrode, and the side coated with the coating faces the positive electrode.